2016
DOI: 10.5604/15093492.1226595
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Causes of Fracture Non-union after Diaphyseal Forearm Fracture Fixation: an in Silico Analysis. Case Study

Abstract: To sum up, we believe that the case described in this paper confirms the limitations to the use of LCP reconstruction plates in patients with well-developed musculature, even in the case of repeat fixation, when good adjustment of the plate well to the axis of the bone appears necessary. It is possible to use an orthosis, first a locking one and then one that limits pronation during further treatment of a partially healed fracture, but, as this case shows, it is not a fully reliable method of preventing compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Faldini et al [23] reported no differences in rate of healing between autografts and allografts in the treatment of 34 adult forearm nonunions undergoing a procedure involving either a fibular autograft (20) or allograft bone strut (14). These results were similar to a comparative study by Piotrowski et al [44], showing no significant differences in the effectiveness and time of bone union between recipients of autogenous or homogenous grafts.…”
Section: Reviewsupporting
confidence: 91%
“…Faldini et al [23] reported no differences in rate of healing between autografts and allografts in the treatment of 34 adult forearm nonunions undergoing a procedure involving either a fibular autograft (20) or allograft bone strut (14). These results were similar to a comparative study by Piotrowski et al [44], showing no significant differences in the effectiveness and time of bone union between recipients of autogenous or homogenous grafts.…”
Section: Reviewsupporting
confidence: 91%